Pengaruh Rotasi dan Promosi Jabatan Terhadap Kinerja Pegawai Serta Implikasinya Terhadap Kinerja Pegawai : Studi pada Dinas Pendidikan Kabupaten Ciamis - Ading Rahman Sukmara; Fanny Fauziyanti; Ferey Herman (Ebisnis Manajemen, 2025)
This study is motivated by several problems that: Employee performance is still low, this is due to several factors, namely the quality of work produced is still not good, lack of leadership direction to subordinates, high employee attendance rate and declining work performance. Low employee work motivation, as evidenced by the amount of time spent during working hours that are not used optimally, still low motivation to increase understanding of work duties and responsibilities, as well as motivation to improve skills in terms of work mastery which can help make it easier to carry out work. The promotion of positions at the Ciamis Regency Education Office is considered to have not fulfilled the predetermined procedures. There are still structural positions that are filled by people who do not have a formal education background or are not in accordance with their competence, this is due to the lack of competent human resources in their fields because people with appropriate formal education, ranks and classes have not been able to occupy structural positions so that they are filled by officials with a formal education background that is not their competence. The implementation of rotation is still optimally organized, it can be seen in the reality that the implementation of rotation often occurs in a spoil system. The spoiler system is a rotation program based on family or based on acquaintances or connections. The results of the study inform that: (1) there is a positive influence of rotation on work motivation. This means that if there is an increase in rotation, it will be followed by an increase in work motivation. (2) there is a positive influence of position promotion on work motivation. This means that if there is an increase, it will be followed by an increase in work motivation. (3) there is a positive influence of rotation and promotion of positions on work motivation. This means that rotation and promotion of positions is one part of formal employee development which aims to provide motivation to employees of the Ciamis Regency Education Office. (4) There is a positive influence of work motivation on employee performance. This means that Motivation is closely related to performance or performance. Employees who have high work motivation can improve performance, on the other hand, employees who do not have motivation to work will reduce performance so that the goals of an agency will not be achieved. The method used in this study is a quantitative descriptive method, including data analysis techniques, namely validity test, reliability test of descriptive analysis, verifiable analysis, multiple linear analysis, f test, t test and path analysis.